A ginseng-derived rhamnogalacturonan I (RG-I) pectin promotes longevity via TOR signalling in Caenorhabditis elegans. (15th July 2023) - Wang, Jiayi; Zhou, Yuwei; Yu, Yang; Wang, Yuan; Xue, Dongxue; Zhou, Yifa; Li, Xiaoxue
Abstract: Panax ginseng C. A. Meyer (ginseng), a traditional Chinese herb, is usually used to improve health and increase anti-aging activity for human. Polysaccharides are bioactive components of ginseng. Herein, using Caenorhabditis elegans as a model, we discovered a ginseng-derived rhamnogalacturonan I (RG-I) pectin WGPA-1-RG promoted longevity via TOR signalling pathway with transcription factors FOXO/DAF-16 and Nrf2/SKN-1 accumulated in the nucleus, where they activated target genes. And the WGPA-1-RG-mediated lifespan extension was dependent on endocytosis, rather than a bacterial metabolic process. Glycosidic linkage analyses combined with arabinose- and galactose-releasing enzyme hydrolyses identified the RG-I backbone of WGPA-1-RG was primarily substituted with α-1, 5-linked arabinan, β-1, 4-linked galactan and arabinogalactan II (AG-II) side chains. Feeding worms with the WGPA-1-RG-derived fractions which lost distinct structural elements by enzymatic digestions, we found the arabinan side chains prominently contributed to the longevity-promoting activity of WGPA-1-RG. These findings provide a novel ginseng-derived nutrient that potentially increases human longevity. Graphical abstract: Unlabelled Image Highlights: A ginseng-derived RG-I pectin WGPA-1-RG extends lifespan in C. elegans . WGPA-1-RG promotes longevity by activating DAF-16 and SKN-1 via TOR signalling. Endocytosis, not bacterial metabolism, is required for WGPA-1-RG-mediated anti-aging. Arabinan side chains contribute to WGPA-1-RG-mediated lifespan extension.